Meruwat Muhammadiyah : kritik seabad gerakan pembaruan Islam di Indonesia - Mu'arif, 1977-; Kamal, Zainun, 1950- (Yogyakarta : Pilar Media, 2005)
Positive criticism for rebuilding internal reform within Muhammadiyah, an Islamic organization in Indonesia.
Includes bibliographical references (p. 313-317) and index.
Keywords: Muhammadiyah (Organization); Indonesia -- Politics and government -- 1998-